2022
DOI: 10.3390/molecules27103125
|View full text |Cite
|
Sign up to set email alerts
|

The Reversible Carnitine Palmitoyltransferase 1 Inhibitor (Teglicar) Ameliorates the Neurodegenerative Phenotype in a Drosophila Huntington’s Disease Model by Acting on the Expression of Carnitine-Related Genes

Abstract: Huntington’s disease (HD) is a dramatic neurodegenerative disorder caused by the abnormal expansion of a CAG triplet in the huntingtin gene, producing an abnormal protein. As it leads to the death of neurons in the cerebral cortex, the patients primarily present with neurological symptoms, but recently metabolic changes resulting from mitochondrial dysfunction have been identified as novel pathological features. The carnitine shuttle is a complex consisting of three enzymes whose function is to transport the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…An animal study revealed that glycolytic striatal astrocytes had reprogrammed their fuel use and switched to FAO as an alternative energy source in HD [ 85 ]. Moreover, behavioral and transcriptional analyses of the HD Drosophila model demonstrated that the availability of lipids for βOX plays an essential role in developing HD symptoms [ 86 ]. In this study, Teglicar, a reversible inhibitor of CPT1A (also known as ST1326), impaired the oxidation of FAs and the availability of cytosolic acetyl-CoA.…”
Section: βOx In Neurodegenerative Diseases and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…An animal study revealed that glycolytic striatal astrocytes had reprogrammed their fuel use and switched to FAO as an alternative energy source in HD [ 85 ]. Moreover, behavioral and transcriptional analyses of the HD Drosophila model demonstrated that the availability of lipids for βOX plays an essential role in developing HD symptoms [ 86 ]. In this study, Teglicar, a reversible inhibitor of CPT1A (also known as ST1326), impaired the oxidation of FAs and the availability of cytosolic acetyl-CoA.…”
Section: βOx In Neurodegenerative Diseases and Agingmentioning
confidence: 99%
“…Therefore, decreased cell reliance on βOX led to a metabolic shift toward glucose oxidation and significantly improved locomotion. It delayed the onset of the disease in the HD Drosophila model [ 86 ].…”
Section: βOx In Neurodegenerative Diseases and Agingmentioning
confidence: 99%
“…Studies have shown that the combination of ST1326 and ABT199 (Bcl-2 inhibitor) can enhance the anti-acute myeloid leukemia (AML) effect of the latter, indicating that cpt1a may become a potential drug target for the treatment of AML (Ricciardi et al, 2015;Mao et al, 2021). Huntington's disease (HTT) is a severe neurodegenerative disease, and a Drosophila HTT disease model was used to demonstrate that treatment with the cpt1a inhibitor ST1326 can alleviate the symptoms of HTT (Bertapelle et al, 2022). Although the relationship between mitochondrial energy metabolism and HTT disease is still unclear, the development of safe and effective CPT1 inhibitors may be an effective strategy to slow down the development of HTT disease.…”
Section: Cpt1mentioning
confidence: 99%